Pengembangan Aplikasi Pemesanan Tiket Travel Berbasis Web dengan Optimasi Jalur Penjemputan Penumpang (Studi Kasus: Beruang Travel) - Della Fauziah; Fajar Pradana; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The progress of the development of technology, especially the Web today, can make competition in the business world increase. In the business world, many companies engaged in transportation services are expected to become a travel business. Management of travel business requires fast customer service, so this business requires the right web information technology to help improve the quality of its service. This information technology optimization strategy for time efficiency is needed to optimize pickup route selection. The Djikstra algorithm is needed to perform calculations to get passenger pickup results based on the closest distance. This travel ticket booking application was developed using the waterfall method where at the defining requirement used an open interview technique. Then at the implementation stage use the MySQL database and the PHP language with the CodeIgniter framework. This functionality tester of this travel ticket booking application, uses unit and integration testing that produce valid values in testing a unit and components that work in the system. In addition, validation testing is also carried out with 100% valid results. While testing non-functional requirements this application uses compatibility testing with the result that there are 2 critical issues in 2 different browsers.